Energetinio saugumo sociologija : teorija ir praktika Sociology of energy security: theory and practice - Genys, Dainius (Vytautas Magnus University, 2017)
The risk, uncertainty and security of the energy system development are the topics which relevance has been determined by the particularly complicated issues of the energy supply and its functioning in contemporary societies under global energy system. The development of the energy sector has always been not only one of the basic conditions for society development, but one of the most serious threats to enormous and multidimensional (economic, health, ecological, social and political) predictable and unpredictable, probable and unexpected multifaceted security issues. The consequences of the positive and negative globalization are particularly evident in the energy sector, both in the provision of cheap and environmentally friendly energy resources, and in the event of harmful and even tragic consequences for the development of the energy system. An important element of energy politics in liberal democratic societies is the public opinion and participation. The perception of energy security in the Lithuanian society is analyzed from rational choice, reflexive modernization, system theory, postmodern perspective, cultural theory, and governance theory points of views. Sociological analysis of energy security is considered to be a relatively separate branch of sociology. It differs from other topics not so much on the particularity of the theoretical approaches, but on the topic itself. It requires specific adaptation of risk theories for the analysis of specific data. The monograph is based on data from two (2013 and 2014) representative Lithuanian society surveys (18 and older). The results reflect the opinion of Lithuanian population distributed by age, sex, place of residence, education, purchasing power and occupation.